Biological synthesis of nanostructured ZnO as a solar-light driven photocatalyst and antimicrobial agent. Issue 10 (15th May 2022) - Sumra, Ayesha Ahmed; Aadil, Muhammad; Ejaz, Syeda Rabia; Anjum, Saima; Saleem, Tahira; Zain, Maryam; Alsafari, Ibrahim A.
Abstract: A good photocatalyst should have a high surface area, a substantial absorption capacity, and a visible light active bandgap. Semi-conductive materials, particularly nanostructured ones, have recently received more attention for photocatalytic applications since they have nearly all of the properties of a perfect photocatalyst. Therefore, modern material scientists attempt to develop a cost-effective and environmentally acceptable method for nanoscale fabrication of semi-conductive materials. Herein, we fabricate a two-dimensional (2D) nanoarchitecture of ZnO by reducing zinc nitrate precursor using plant extract ( Cleome brachycarpa ). Flavonoids are antioxidants that are found in high amounts in the roots, leaves, and stems of Cleome brachycarpa . Crystal structure, morphological characteristics, elemental compositions, and functional group analyses of the as-synthesized ZnO sample were carried out using X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive X-ray (EDX), Fourier transform infrared (FTIR), and other techniques. XRD analysis confirmed that ZnO with a nano-crystallite size (18.377 nm) and a wurtzite phase had been formed successfully. The FTIR and UV–visible analyses of the as-prepared ZnO nanoarchitecture verify the nanoarchitecture's Zn–O vibrational mode and visible light-triggered band gap (2.89 eV), respectively. SEM and EDX examinations validated the sample's two-dimensional nanoarchitecture and impurity-free chemical composition, respectively. The photocatalytic efficiency of the ZnO was analyzed under solar against crystal violet dye (CV) for 70 min. Briefly, the nanostructured ZnO catalyst eliminated 88.4% CV (mineralization + adsorption) at the rate constant (k) of 0.022 min -1 . Agar well diffusion was employed to evaluate the antibacterial potential of the produced ZnO sample, which proved to be effective against both G + ive and G-ive bacterial strains. ZnO's exceptional photo-mineralization and antibacterial characteristics are owing to its innovative 2D nanoarchitecture, and visible-light triggered bandgap. The production of nanostructured semi-conductive materials from naturally occurring plant products might be advocated as an environmentally friendly alternative to chemical techniques in the future. Graphical abstract: Image 1